Microstructure and Mechanical Properties of Friction Crush Welded Joints of Oxygen-Free Copper (C1020) Sheets - Abduljabbar S. Joma; Akeel Dhahir Subhi; Fadhil Abbas Hashim (Diyala Journal of Engineering Sciences, 2020)
Friction crush welding applications (FCW) provides versatile applications in sheet metals welding. In this work, different tool rotational speeds (220, 410, 920, 1500 rpm) and feed rates (20, 43, 80,150 mm/min) were used to weld oxygen-free copper sheets with flanged edges. Evaluation of Cu-Cu joints was performed successfully using optical microscope, vickers hardness and tensile test. The results showed that the microstructure was significantly influenced by welding parameters used. Different defects were recognized in the welding zone. The highest hardness of 63 HV and tensile strength of 105 MPa were obtained at tool rotational speed of 1500 rpm and feed rate of 115 mm/min.